Comparison Between Procalcitonin and Traditional Blood Biomarkers in Diagnosis of Sepsis in Iraqi Wounded Soldiers - Jasem, Meroj A.; Mahmood, Alia E.; Mahmood, Ayser I.; Mustafa, Mahmood M.; Farhood, Khalid M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Early diagnosis of sepsis is a very critical matter especially for soldiers in battle field; on the other hand, Procalcitonin is a new promising biomarker for fast and accurate diagnosis of sepsis. The aim of this study is to investigate the ability of Procalcitonin (PCT) to indicate sepsis earlier than blood culture and other traditional biomarkers and then get use of this in early diagnosis of sepsis.Procalcitonin concentration was measured in 44 sera of Iraqi wounded soldiers who were admitted to GHAZI AL-HARIRI Hospital for surgery, using ELISA kit of BioRay/USA, along with blood culture and other infection biomarker like C-reactive protein, ESR, W.B.C. count. Six patients had elevated PCT and 3 of them had positive blood culture, two of these three died. PCT has good correlation with other inflammatory biomarkers. It is our recommendation to accredit PCT as a very early biomarker of sepsis in Iraqi hospitals along with blood culture but earlier than it, and to use the quick test of PCT in battlefield to determine the priority of transmission of wounded soldiers to hospitals.